Perbedaan Pengaruh Interval Walking Training dan Aerobic Exercise terhadap Penurunan Kadar Kolesterol Total pada Individu dengan Risiko Stroke - Nabila Safamala Andiva; Ganesa P.D. Kurniawan; R. Trioclarise; Restu Arya Pambudi (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Stroke is one of the leading causes of death and disability worldwide and is closely associated with elevated total cholesterol levels as a major risk factor. Prevention efforts can be carried out through non-pharmacological interventions such as physical exercise, including Interval Walking Training (IWT) and Aerobic Exercise. Objectives: To determine the difference in the effects of Interval Walking Training and Aerobic Exercise on reducing total cholesterol levels in individuals at risk of stroke. Methods: This study used a quasi experimental design with two intervention groups. The study was conducted in RW 10, Ciracas, East Jakarta. A total of 50 participants aged 45–70 years were divided into IWT and Aerobic Exercise groups. The interventions were conducted for 4 weeks with a frequency of 2 times per week. Total cholesterol levels were measured before and after the intervention using a digital cholesterol meter. Data were analyzed using Paired t-test/Wilcoxon and Mann-Whitney test. Result: Both interventions showed a reduction in total cholesterol levels after treatment. However, the Aerobic Exercise group demonstrated a greater reduction compared to the IWT group. There was a difference in effect between the two groups, although individual response variations were observed. Conclusion: Aerobic Exercise is more effective than IWT in reducing total cholesterol levels in individuals at risk of stroke. Keywords: Stroke, Total Cholesterol Levels, IWT, Aerobik Exercise, Stroke Risk.